Harnessing the Effect of Adoptively Transferred Tumor-Reactive T Cells on Endogenous (Host-Derived) Antitumor Immunity - Yolanda Nesbeth; Jose R. Conejo-Garcia (Clinical and Developmental Immunology)
Adoptive T cell transfer therapy, the ex vivo activation, expansion, and subsequent administration of tumor-reactive T cells, is already the most effective therapy against certain types of cancer. However, recent evidence in animal models and clinical trials suggests that host conditioning interventions tailored for some of the most aggressive and frequent epithelial cancers will be needed to maximize the benefit of this approach. Similarly, the subsets, stage of differentiation, and ex vivo expansion procedure of tumor-reactive T cells to be adoptively transferred influence their in vivo effectiveness and may need to be adapted for different types of cancer and host conditioning interventions. The effects of adoptively transferred tumor-reactive T cells on the mechanisms of endogenous (host-derived) antitumor immunity, and how to maximize their combined effects, are further discussed.